2012
DOI: 10.1016/j.etp.2010.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Urban air pollution produces up-regulation of myocardial inflammatory genes and dark chocolate provides cardioprotection

Abstract: Air pollution is a serious environmental problem. Elderly subjects show increased cardiac morbidity and mortality associated with air pollution exposure. Mexico City (MC) residents are chronically exposed to high concentrations of fine particulate matter (PM 2.5 ) and PM-associated lipopolysaccharides (PM-LPS). To test the hypothesis that chronic exposure to urban pollution produces myocardial inflammation, female Balb-c mice age 4 weeks were exposed for 16 months to two distinctly different polluted areas wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 72 publications
(107 reference statements)
1
37
1
Order By: Relevance
“…In the present study, we show that emodin treatment abrogated the DEPinduced increase in cardiac proinflammatory cytokine TNFα and IL1β. It has been recently demonstrated that air pollution exposure induces myocardial inflammation characterized by increase of TNFα and IL1β and that dark chocolate provides cardioprotection [40].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we show that emodin treatment abrogated the DEPinduced increase in cardiac proinflammatory cytokine TNFα and IL1β. It has been recently demonstrated that air pollution exposure induces myocardial inflammation characterized by increase of TNFα and IL1β and that dark chocolate provides cardioprotection [40].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that chocolate administration significantly downregulates TNF-α, IL-6, and IL-1β expression in mice exposed to urban air pollution, indicating that polyphenolic antioxidants could reduce cardiac inflammation caused by exposure to air pollution [19]. An extract of Eucheuma cottonii reduces both the accumulation of alveolar macrophages and the serum levels of malondialdehyde in PM10 coal dust-exposed rats, indicating that the extract attenuates inflammation and oxidative stress resulting from chronic coal dust exposure [26].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous plant-derived polyphenolic compounds exhibit antioxidant and anti-inflammatory effects [17-19]. We previously reported that pomegranate peel extract attenuates the oxidative and inflammatory responses of monocytes exposed to PM10 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of the endogenous antioxidant superoxide dismutase attenuates the vascular effects of C-DEAP particles in isolated blood vessels (205). Furthermore, emerging data from animal models suggests that several antioxidant(-rich) compounds, including curcumin (242), NAC (243), NAD(P)H oxidase inhibitors (244), vanillic acid (245), emodin (246), tempol (235), and even dark chocolate (247), can protect against some cardiovascular actions of C-DEAP. Regrettably, these findings have not been replicated in human studies, with antioxidant-rich foods or supplements having inconsistent effects on PM 2.5 -induced heart rate variability (248,249) and vascular dysfunction (250252).…”
Section: Role Of Oxidative Stress In the Cardiovascular Effects Of Aimentioning
confidence: 99%